Digital Teachers from the Perspective of Applied Ethics - Anita Indria; Afni Lindra; Arif Ridha; Ardi Satrial (Ahlussunnah: Journal of Islamic Education, 2026)
The rapid development of digital technology has brought significant changes to the world of education, particularly in how teachers deliver content and interact with students. The emergence of various digital platforms, social media, and educational content creators has made learning resources increasingly diverse and easily accessible to students. This situation requires teachers to be able to adapt to technological developments while upholding the ethical values of the teaching profession. This study aims to examine the role of digital teachers from the perspective of applied ethics and to explain how ethical principles can serve as a foundation for teachers to utilize technology wisely and professionally. This study employs a qualitative method using a literature review approach, drawing from books, scientific journals, research articles, and various relevant literature on professional teaching ethics and the use of digital technology in education. The study’s findings indicate that teachers’ use of technology must be grounded in the principles of responsibility, academic integrity, privacy protection, equitable access to technology, and professionalism in interacting with students. Furthermore, teachers serve as knowledge curators who select and evaluate digital content before it is used in instruction. From an applied ethics perspective, digital teachers function not only as technology users but also as moral agents who ensure that the integration of technology remains aligned with educational goals, character development, and the cultivation of students’ critical thinking skills. Therefore, an adaptive, critical, and responsible attitude is key for teachers in utilizing digital technology ethically and professionally within the educational process.